Teaching history well: characteristics of high-quality secondary and middle level teachers of history - Burenheide, Bradley (My University, 2011)
This exploratory qualitative study serves as a beginning to the discussion of what teachers of history do well. This study involved the interviewing and reviewing of materials from secondary level teachers of history who have been identified by their peers as outstanding teachers of history. The study focused on the following three questions: 1. What are the methods employed by “good teachers of history?” 2. What are the core beliefs regarding the teaching of history possessed by “good teachers of history?” 3. Are the traits and characteristics of “good teachers of history” inherent or could they be learned and developed? The findings of the study show these high quality teachers of history have their students explore the discipline of history, believe strongly in the lessons gleaned from historical study, and provide hope that these characteristics can be learned and encouraged in young teachers in the training and induction phase of teacher education.
Keywords: History teaching; Teaching methods; Grounded theory research